Brand Talkedness: How likely is your brand to be talked about by the public? - Bambang Sukma Wijaya (Jobmark: Journal of Branding and Marketing Communication, 2019)
Brand talkedness is the degree to which a brand is being talked about by its customers, potential customers, and the public. It is a measure of the brand’s word-of-mouth popularity and influence. Brand talkedness can be influenced by many factors, such as the brand’s voice, personality, storytelling, content, and customer experience. A brand with high talkedness can benefit from increased awareness, loyalty, trust, and sales. However, not all talkedness is positive. A brand can also generate negative word-of-mouth if it fails to meet customer expectations, behaves unethically, or faces a crisis. Therefore, a brand should monitor and manage its talkedness carefully to ensure that it reflects its desired image and reputation. This article describes the insightful concepts for brand talkedness so researchers and practitioners can correctly measure, manage, and develop brand talkedness strategies.